Feasibility Study of Biomass Fly Ash as a Partial Cement Replacement in Mortar Cured in Seawater - Dahlia Patah; Amry Dasar; Nur Okviyani; Apriansyah Apriansyah; Nurazuwa Md Noor (Borneo Engineering: Jurnal Teknik Sipil, 2026)
The high consumption of cement and the limited utilization of biomass combustion residues have highlighted the need for the development of more sustainable cement materials, particularly for construction in coastal areas. While biomass fly ash (BFA) has potential as a cement replacement material, information regarding the use of raw BFA, without pretreatment, in mortar cured in seawater remains limited. This study aims to evaluate the technical feasibility of BFA as a partial cement replacement in mortar, based on compressive strength, ultrasonic pulse velocity (UPV), water absorption, and strength activity index (SAI). BFA was used to replace cement at levels of 10%, 20%, and 30% by weight. Mortar mixtures were prepared with a water-to-cement ratio of 0.40, using tap water for mixing and seawater as the curing medium. Compressive strength was tested at 7, 28, and 91 days, while UPV and water absorption were tested at 28 and 91 days. The SAI values were calculated from the compressive strength results to assess the effectiveness of BFA as a cement replacement material. The results indicated that mortar performance was significantly influenced by the BFA substitution level. The mixture with 10% BFA exhibited the best performance, achieving a compressive strength of 32.62 MPa at 91 days, a UPV value of 3434 m/s, and water absorption of 4.80%. The mixture with 20% BFA still showed reasonably good performance, whereas the 30% BFA mixture led to a noticeable deterioration in mortar quality. The SAI results confirmed that 10% replacement was the most effective level. These findings indicate that raw BFA can be directly utilized as a partial cement replacement in mortar cured in seawater.